2014
DOI: 10.1038/srep05053
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties and energy transfer parameters of Er3+- doped fluorozirconate and oxyfluoroaluminate glasses

Abstract: Er3+- doped fluorozirconate (ZrF4-BaF2-YF3-AlF3) and oxyfluoroaluminate glasses are successfully prepared here. These glasses exhibit significant superiority compared with traditional fluorozirconate glass (ZrF4-BaF2-LaF3-AlF3-NaF) because of their higher temperature of glass transition and better resistance to water corrosion. Judd-Ofelt (J-O) intensity parameters are evaluated and used to compute the radiative properties based on the VIS-NIR absorption spectra. Broad emission bands located at 1535 and 2708 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 53 publications
0
30
2
Order By: Relevance
“…The Ω 2 values of the title glasses increase from 2.33 to 4.76 with the increase in Er 3+ ion concentration and are found to be higher than the reported oxyfluorozirconate (3.01) [31], SLBiB1.5E (3.91) [32], Bismuth borate (3.24) [33], Lithium borate (3.24), CaLiBO (3.68) [34], Zinc bismuthborate (3.94) [35] and sodalime silicate (2.72) [36] glasses indicating the higher asymmetry and increasing degree of covalency of the ligand field around the Er 3+ ion site. The variation of Ω 2 parameter and transition strength of the hypersensitive transition with varying Er 3+ ion concentrations are shown in Fig.…”
Section: Oscillator Strengths and Judd-ofelt Parameterscontrasting
confidence: 67%
“…The Ω 2 values of the title glasses increase from 2.33 to 4.76 with the increase in Er 3+ ion concentration and are found to be higher than the reported oxyfluorozirconate (3.01) [31], SLBiB1.5E (3.91) [32], Bismuth borate (3.24) [33], Lithium borate (3.24), CaLiBO (3.68) [34], Zinc bismuthborate (3.94) [35] and sodalime silicate (2.72) [36] glasses indicating the higher asymmetry and increasing degree of covalency of the ligand field around the Er 3+ ion site. The variation of Ω 2 parameter and transition strength of the hypersensitive transition with varying Er 3+ ion concentrations are shown in Fig.…”
Section: Oscillator Strengths and Judd-ofelt Parameterscontrasting
confidence: 67%
“…Similarly, the NIR/MIR emission of Er 3+ /Yb 3+ ‐doped β‐NaYF 4 microcrystals is studied and the effects of Er 3+ /Yb 3+ concentrations on NIR/MIR emission intensity are discussed as shown in Figure . Under the pumping by a 976 nm LD, an emission at 1.5 μm due to the Er 3+ : 4 I 13/2 → 4 I 15/2 transition is clearly observed as shown in Figure . In Figures A,B, it is found that with the increase of Er 3+ concentrations form 0.25 to 3 mol% in β‐NaYF 4 microcrystals the 1.5 μm emission intensity increases remarkably, but the 1.5 μm emission intensity decreases with further increase of Er 3+ concentration.…”
Section: Resultsmentioning
confidence: 95%
“…NIR luminescent lanthanide materials are in the range of 0.78‐2.5 μm, which receive great attention in wide applications for fiber optical communication, solid‐state laser and fluoroimmunoassay due to its unique narrow line width and long lifetime . The range of MIR luminescence is 2.5‐25 μm, which are potentially important in military and atmosphere pollution monitoring applications . And to our best knowledge, MIR emission has been previously reported in other materials, such as Re‐doped glass or fiber, no any study is reported about the MIR emission of Re‐doped NaYF 4 microcrystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tg of this sample is 520°C. It exhibits higher Tg than tellurites [19] and fluorides [20], thus demonstrates higher laser damage threshold. No crystallization peak appears as the temperature increases to 850°C, indicating the high stability of the sample against crystallization.…”
Section: Thermal Stabilitymentioning
confidence: 99%